2019
DOI: 10.3800/pbr.14.224
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in phytoplankton carbon biomass and primary production, and their contribution to particulate carbon in the neritic area of Sagami Bay, Japan

Abstract: Seasonal variations in environmental variables, chlorophyll a (Chl-a), particulate carbon and nitrogen (PC and PN, respectively), phytoplankton carbon biomass (Ph-C) and primary production were investigated at a neritic station in Sagami Bay, Kanagawa, from January 2008 to December 2013. Size-fractionated Ph-C was converted from cell volume by microscopic observation, adding valuable data for this area. During spring blooms, the micro-size fraction (>20 µm) comprised the majority of the total Chl-a and total P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…Cyanobacteria were relatively abundant in clusters 2 and 3-1, accounting for up to 61% and DBRDA ordination revealed that cyanobacteria (Synechococcus_ CC9902) were highly correlated with water temperature. The sporadic increase of cyanobacteria from summer to autumn is consistent with previous studies in the same Sagami Bay area (Mitbavkar et al 2009;Ara et al 2019). Cyanobacterial abundance and growth rate are dependent principally on the temperature (Chen and Liu 2010;Chen et al 2014;Wang et al 2020).…”
Section: Bacterial Communitysupporting
confidence: 90%
“…Cyanobacteria were relatively abundant in clusters 2 and 3-1, accounting for up to 61% and DBRDA ordination revealed that cyanobacteria (Synechococcus_ CC9902) were highly correlated with water temperature. The sporadic increase of cyanobacteria from summer to autumn is consistent with previous studies in the same Sagami Bay area (Mitbavkar et al 2009;Ara et al 2019). Cyanobacterial abundance and growth rate are dependent principally on the temperature (Chen and Liu 2010;Chen et al 2014;Wang et al 2020).…”
Section: Bacterial Communitysupporting
confidence: 90%
“…In particular, nitrate and phosphate were three and two times higher, respectively (Table 1). These nutrient conditions are favorable for phytoplankton growth, and microplankton such as diatom and dinoflagellate blooms have been previously reported in Sagami Bay (Satoh et al 2000, Ara et al 2019. Ogura & Sato (2001) concluded that the nitrate and nitrite concentrations at the time of the coccolithophore bloom in May 1995 were higher than May 1994, when dinoflagellates and diatoms were the dominant bloom-forming groups.…”
Section: Bloom Sustainment In Sagami Baymentioning
confidence: 52%
“…The study supports the hypothesis that G. huxleyi is a good competitor at low nitrogen concentrations, since these conditions limit diatom growth. In Sagami Bay, microplankton (mainly diatoms) caused an annual spring bloom from February to May (2008May ( -2013, when nutrient concentrations declined considerably (Ara et al 2019). Thus, although nutrients tend to deplete in Sagami Bay in May after spring blooms, our results indicated that the concentrations of nitrate and nitrite were relatively high in May 2020.…”
Section: Bloom Sustainment In Sagami Baymentioning
confidence: 63%
See 1 more Smart Citation